2012
DOI: 10.1021/mz300397h
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Polysiloxane Architectures from Spirosiloxane Precursors via Intramolecular Hydrosilylation

Abstract: In this letter a method is described to synthesize new polysiloxane architectures by photoacid catalysis. An oxasilaspirocycle is designed that is able to undergo a photoacid generator catalyzed ring-opening reaction leading to either a homopolymer or to copolymers with hydroxyl-terminated polydimethylsiloxane. These polymers feature a defined amount of double bonds in the backbone, which is controlled by the ratio of oxasilaspirocycle to the comonomer. The former was prepared by trispentafluorophenylborane-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Typical examples are triphenylsulfonium triflate and diphenyliodonium triflate. The latter has been studied recently [66] to selectively cleave the carbon-oxygen bonds in a vinyl functionalized oxasilaspirocycle to form both homo-and copolymer polysiloxanes via a double ring-opening CROP (cf. Section 2.3, see Figure 23).…”
Section: Lewis Acidsmentioning
confidence: 99%
“…Typical examples are triphenylsulfonium triflate and diphenyliodonium triflate. The latter has been studied recently [66] to selectively cleave the carbon-oxygen bonds in a vinyl functionalized oxasilaspirocycle to form both homo-and copolymer polysiloxanes via a double ring-opening CROP (cf. Section 2.3, see Figure 23).…”
Section: Lewis Acidsmentioning
confidence: 99%
“…By avoiding the synthesis and manipulation of long chain polymers, this approach offers the chance to take the benefit of good virtues of small molecules, such as low viscosity, good miscibility, and high purity, and has therefore been increasingly drawing attention from the scientific community. [3][4][5][6][7][8][9][10][11][12][13][14][15] The ring opening reaction of multiple-ring small cyclic molecules provides an additional and versatile approach to prepare crosslinked polymeric materials directly from small molecules. Single ring cyclic molecules lead to linear polymers when they are rendered to ring-opening reactions, but those with two or more rings will generate crosslinked materials in the presence of suitable catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The popular epoxy resin is actually made in this way, and its successful commercialization has served to excite researchers to investigate deeper in this direction. Until now, numerous multiple-ring cyclic molecules other than epoxides [2][3][4][5][6][7][8] have been reported with demonstrated use in the preparation of novel polymers and advanced materials. [9][10][11][12][13] For example, Yang et al reported the formation of biodegradable polycarbonate network by the crosslinker molecule, bis(trimethylene carbonate), and investigated the relationship between the amount of the crosslinker and the degradation rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Therefore ladder-like polysiloxane may be a suitable structure for developing new high-performance ame retardants. However, polysiloxanes generally have considerably different solubility parameters to other polymers, 19 leading to difficulties in endowing the modied polymers with the outstanding properties of polysiloxanes due to poor dispersion. Hence, to be a good ame-retardant, ladder-like polysiloxane should have functional groups that can react with the polymer.…”
Section: Introductionmentioning
confidence: 99%